Ocena wybranych zachowań zdrowotnych przez i po zdiagnozowaniu choroby wśród kobiet z nowotworem piersi w oparciu o Inwentarz Zachowań Zdrowotnych Juczyńskiego – badanie wstępne = Evaluation of selected health behaviors before and after the diagnosis among women with breast cancer based on the Health-Related Behaviour Inventory (HBI) questionnaire developed by Juczyński - preliminary study - Bojakowska, Urszula Jolanta; Kalinowski, Paweł; Kowalska, Marta Estera (Journal of Education, Health and Sport, 2016)
Bojakowska Urszula, Kalinowski Paweł, Kowalska Marta Estera. Ocena wybranych zachowań zdrowotnych przez i po zdiagnozowaniu choroby wśród kobiet z nowotworem piersi w oparciu o Inwentarz Zachowań Zdrowotnych Juczyńskiego – badanie wstępne = Evaluation of selected health behaviors before and after the diagnosis among women with breast cancer based on the Health-Related Behaviour Inventory (HBI) questionnaire developed by Juczyński - preliminary study. Journal of Education, Health and Sport. 2016;6(5):29-37. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50958 http://ojs.ukw.edu.pl/index.php/johs/article/view/3507 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 04.05.2016. Ocena wybranych zachowań zdrowotnych przez i po zdiagnozowaniu choroby wśród kobiet z nowotworem piersi w oparciu o Inwentarz Zachowań Zdrowotnych Juczyńskiego – badanie wstępne Evaluation of selected health behaviors before and after the diagnosis among women with breast cancer based on the Health-Related Behaviour Inventory (HBI) questionnaire developed by Juczyński - preliminary study Urszula Bojakowska1,2, Paweł Kalinowski1, Marta Estera Kowalska1 1. Samodzielna Pracownia Epidemiologii Uniwersytet Medyczny w Lublinie 2. SKN przy Samodzielnej Pracowni Epidemiologii, Uniwersytet Medyczny w Lublinie Słowa kluczowe: rak piersi, zachowania zdrowotne, profilaktyka Key words: brest cancer, health behaviors, prophylaxis Abstrakt Cel pracy Celem pracy była ocena wybranych zachowań zdrowotnych przed i po leczeniu wśród kobiet z nowotworem piersi. Materiał i metoda W badaniu zastosowano metodę sondażu diagnostycznego z techniką ankiety. Do realizacji badań posłużył kwestionariusz Inwentarz Zachowań Zdrowotnych (IZZ) Juczyńskiego. Badaniami objęto 70 kobiet z rakiem piersi, w przedziale wieku między35 a77 rokiem życia zamieszkujących województwo lubelskie. Analizy statystyczne przeprowadzono w oparciu o program Statistica 10.0. Wyniki W oparciu o skalę IZZ przed chorobą wyniki niskie uzyskało 80% badanych, przeciętne – 11,4%, zaś wysokie – 8,6%. Po rozpoznaniu choroby wyniki niskie uzyskało 17,1%, przeciętne – 30%, a wysokie 52,9%. Wskaźnik zachowań zdrowotnych dla ogółu badanych wyniósł średnio 66,23 przed chorobą i 90,5 po rozpoznaniu. Po rozpoznaniu choroby we wszystkich kategoriach uzyskano wyższe wyniki niż przed. Wnioski Doświadczenia związane z chorobą mają istotny wpływ na wzrost ogólnego wskaźnika nasilenia zachowań zdrowotnych wśród kobiet z nowotworem piersi. Po rozpoznaniu choroby we wszystkich analizowanych kategoriach zaobserwowano wyższy poziom deklarowanych zachowań zdrowotnych. Abstract Aim The aim of this study was to evaluate selected health behaviors before and after diagnosis of the disease among women with breast cancer. Material and methods In the study the diagnostic survey method was applied in combination with the questionnaire technique. To conduct the research we used Juczyński’s inventory of health behaviours questionnaire. The survey included 77 women with breast cancer, aged from 35 to 77, living in the Lubelskie Voivodeship. The statistical analyses were conducted with the use of the Statistica 10.0 software. Results On the basis of the HBI scale low results obtained 80% of the respondents before the disease, medium - 11.4%, high - 8.6%. After diagnosis, low results obtained 17.1%, medium - 30% and high - 52.9%. The average index of health behaviors for the examination group was 66.23 before the disease and 90.5 after. After diagnosis, in all categories obtained better results than before. Conclusions Experience with the disease have a significant impact on the growth rate of the overall severity of health behavior among women with breast cancer. After diagnosis in all analyzed categories was observed a higher level of declared health behaviors.